The alchemist - Bacigalupi, Paolo (Subterranean Press, 2011)
"In the beleaguered city of Khaim, a lone alchemist seeks a solution to a deadly threat....Every time a spell is cast, a bit of bramble sprouts, sending up tangling vines, bloody thorns, and threatening a poisonous sleep"--From publisher's description on jacket flap.